Heat and mass transfer in MHD flow by natural convection from a permeable surface with heat generation effects - ABDELKHALEK, M. M. (Engineering Transactions, 2008)
The objectives of the present study are to investigate steady two-dimensional laminar flow of a viscous incompressible, electrically conducting and heat-generating fluid, driven by a continuously moving porous plate immersed in a fluid-saturated porous medium, in the presence of a transverse magnetic field. A uniform magnetic field acts perpendicularly to the porous surface which absorbs fluid with a suction velocity. The non-linear partial differential equations governing the problem under consideration have been transformed by a similarity transformation into a system of ordinary differential equations, which is solved numerically by applying a perturbation technique. The effects of material parameters on the velocity and temperature fields across the boundary layer are investigated [28, 29]. A parametric study of all the governing parameters is carried out and representative results are illustrated to reveal a typical tendency of the solutions. Representative results are presented for the velocity temperature distributions as well as the local friction coefficient and the local Nusselt number. Favorable comparisons with the previously published work confirm the correctness of the numerical results.